Studi kelayakan strategis dan finansial SFBilliard untuk meraih keunggulan bisnis - Ferry Octaviana; Nur Nur (Universitas Kristen Maranatha, 2025)
This study investigates the business potential of SFBilliard in Bandung, an emerging indoor sports venture. Its primary objective is to assess financial feasibility and business strategies through SWOT and capital budgeting analyses. Employing a descriptive quantitative methodology, data was collected from 122 respondents (general public, billiard players, and athletes) via questionnaires and semi-structured interviews with owners, employees, customers, and athletes at the research site in Pasteur, Bandung, during May-June 2024. Financial analysis revealed high project feasibility, indicated by a positive net present value (NPV) of IDR5,728,333,639, a rapid payback period (PP) of 24 months and 8 days, an internal rate of return (IRR) of 128.72% (exceeding the 35% cost of capital), and a profitability index (PI) of 3.8338. The initial investment required for equipment was estimated at IDR1,283,400,000. Furthermore, the SWOT analysis identified appropriate strategies to meet consumer demands, such as providing smoke-free areas, managing executive and VIP class types, and implementing digital systems for brand building. It is concluded that SFBilliard is financially viable for implementation and has the potential to become a leading destination for billiard enthusiasts in Bandung, with the implication that the recommended strategies will significantly support the business's growth and sustainability.